2021
DOI: 10.3390/biom12010019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Semi-Quantitative Scoring and Artificial Intelligence Aided Digital Image Analysis of Chromogenic Immunohistochemistry

Abstract: Semi-quantitative scoring is a method that is widely used to estimate the quantity of proteins on chromogen-labelled immunohistochemical (IHC) tissue sections. However, it suffers from several disadvantages, including its lack of objectivity and the fact that it is a time-consuming process. Our aim was to test a recently established artificial intelligence (AI)-aided digital image analysis platform, Pathronus, and to compare it to conventional scoring by five observers on chromogenic IHC-stained slides belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The images were acquired using Olympus I × 71 (Olympus, Japan). The immunohistochemical staining score was graded according to the German semi-quantitative scoring system 52 .…”
Section: Methodsmentioning
confidence: 99%
“…The images were acquired using Olympus I × 71 (Olympus, Japan). The immunohistochemical staining score was graded according to the German semi-quantitative scoring system 52 .…”
Section: Methodsmentioning
confidence: 99%
“…There are four main processes in whole slide imaging to produce a complete digital image: image acquisition, storage, splicing processing, and visualization (27). Several studies have shown that diagnoses derived from digital images of frozen sections or paraffin sections are highly consistent with those from microscopic field interpretation (28)(29)(30)(31)(32). However, each whole slide image (WSI) contains enormous amount of information, relying only on the pathologist's visual inspections for cancer detection, tumor staging and grading, and other analyses would take a lot of time and effort.…”
Section: Digital Pathologymentioning
confidence: 99%
“…Finally, frameworks based on deep learning approaches [25,26] have been also developed. Two important limitations of deep learning models are that they require a large amount of images for model training, and that the model should be applicable to stainings from any type of protein and tissue and generalizable to datasets generated by different laboratories.…”
Section: Related Workmentioning
confidence: 99%
“…The results obtained are promising although limited to that specific type of tissue. In [26], a Convolutional Neural Network (CNN) was employed to annotate the IHC images of neurons. The system first recognizes and crops the stained neurons with the CNN; then, it obtains the cytoplasmatic DAB signal by deconvolution, and finally, it measures the average intensity of the cytoplasm of the neurons.…”
Section: Related Workmentioning
confidence: 99%